Visual function and course of basal laminar drusen combined with vitelliform macular detachment. Issue 6 (June 1994) - Cohen, S Y; Meunier, I; Soubrane, G; Glacet-Bernard, A; Coscas, G J
Abstract : Basal laminar drusen (BLD) are small round yellow drusen that are more easily visualised angiographically than biomicroscopically, with a 'stars in the sky' pattern. Patients with BLD are predisposed to macular vitelliform detachment. Little is known about the course of the disease, but the prognosis for retention of useful central vision for patients with BLD is thought to be better than for patients with typical drusen. A retrospective analysis of clinical and angiographic charts of 19 patients with BLD combined with a vitelliform macular detachment was performed to precisely describe their course. In addition, nine patients were re-examined to allow an analysis of their visual function–that is, central visual field, contrast sensitivity, and colour vision. Eyes without choroidal new vessels retained a fair visual acuity (mean final visual acuity 0.5; follow up 4 to 69 months, mean 24 months). In 11 of these eyes visual function assessment disclosed a reduction of contrast sensitivity in high and medium spatial frequencies in nine eyes (81%), a blue-yellow dyschromatopsia in nine eyes (81%), and a mild reduction of foveal threshold in seven eyes (63%). Choroidal neovascularisation (CNV) was observed in 12 eyes (31%) with a poor final outcome (mean final visual acuity 0.1). Two thirds of cases of CNV were observed at the time of presentation; thus this finding may be a bias of a referring centre. However, the high prevalence of CNV suggests the need for a close follow up of patients with BLD.